BILATERAL REFLEX SYMPATHETIC DYSTROPHY SYNDROME : A Case Report - Duygu Geler; Birkan Sonel Tur; Şehim Kutlay (Archives of Rheumatology, 2003)
Reflex sympathetic dystrophy is a syndrome characterized by swelling, pain and vasomotor changes of the affected extremities. Diagnosis is usually based on clinical signs and symptoms. Successful treatment depends on early diagnosis as well as prevention of secondary complications. 56 year old man with severe pain in his both feet (pronounced in right foot) was admitted to the hospital. He complained of burning pain, hyperalgesia, paresthesia, swelling and occasionally discoloration of the lower ekstremities. Eight months ago, all of his symptoms commenced after the onset of low back pain which showed radiation to the right foot. Occurence of reflex sympathetic dystrophy syndrome (RSDS) secondary to low back pain and bilateral involvement is very rare. Since effective treatment of RSDS largely depends on early diagnosis, clinicians should get suspicious about this syndrome whenever they confront with vazomotor changes accompanying low back pain.